Study on satellite adaptive nulling antennas with hybrid genetic algorithm - JIN Jun1; WANG Hua-li1; DUAN Tao2; LIU Yun-zhi1 (Tongxin xuebao)
Combining genetic algorithm with LMS,a hybrid genetic algorithm（GALMS）for satellite adaptive nulling antenna beam space was proposed.The hybrid algorithm performance of various parameter selections was studied.At last a simultaneous parameter adaptation scheme was introduced.The scheme could reduce difficulty and improve effi-ciency of parameter selection and can dynamically adjust the parameters for better anti-jamming performance.